(untitled) (Indian Journal of Animal Production and Management, 2015)
A total of 120 day old chicks were utilized to evaluate the production performance of Vanaraja chickens under different rearing systems viz. cage, deep litter and semi intensive during 2009. The overall mean body weight, feed conversion ratio were recorded as 1323+28.02, 1238.12+46.02 and 1283.00+26.30 g; and 2.27, 2.44 and 2.05 for cage, deep litter and semi intensive systems respectively. Overall feed conversion ratio (FCR), protein efficiency ratio (PER) and energy efficiency ratio (EER) was significantly better (P<0.05) in T3 group than T1 and T2 groups. The dressing percentage was found to be non- significant among the groups. The weight of giblet, bursa and spleen were significantly (P<0.05) heavier in T3 groups (reared in semi-intensive) than T1 (reared in cages) and T2 groups(reared in deep litter). Net profit per bird in cage, deep litter and semi intensive systems was Rs.18.87, Rs.12.40 and Rs.23.54 respectively. The results suggested that Vanaraja chickens could be reared more economically in semi intensive system.